Synthesis and research of the physical-chemical properties of 5-((2-bromphenyl)-4-amino-4H-1,2,4-triazole-3-ylthio)acetic acid salts - Ye. S. Pruglo (Zaporozhye State Medical University, 2018)
At this stage of the development of modern science the scientists get a lot of questions in the field of medicine and pharmacy, and one of the most important among them is the study and search of new ways of synthesis of high-performance and low-toxic substances. Special attention is paid to 1,2,4-triazole and xanthine. On their basis some medical drugs were made, which are widely used in medicine. The aim of this work was the synthesis and study of properties of salts of 5-(2-bromophenyl)-4-amino-4H-1,2,4-triazole-3-ylthio)acetic acid. Methods and results. As starting material theophylline was selected. Through a number of stages 5-(2-bromphenyl)-4-amino-4H-1,2,4-triazole-3-thion was obtained. By the reaction of neutralization the salts with organic and inorganic bases were obtained. The physical-chemical properties of the compounds were determined. The structure of the substances was confirmed by elemental analysis on an Elementar Vario L cube (CHNS) instrument; IR spectra (4000-400 cm-1) were taken on the ALPHA-T modules of the Bruker ALPHA FT-IR spectrometer. The 1H NMR spectra of the compounds were recorded using a Varian Mercury VX 200 spectrometer (solvent - DMSO-d6, internal standard: tetramethylsilane). The formation of salts was confirmed by the signals of the corresponding protonated amines. Chromato-mass spectral studies were carried out on the LC MS: Agilent 1260 Infinity HPLC System , ionization method - chemical ionization at atmospheric pressure (APCI). Conclusions. The interaction of the resulting thiol with monochloracetic acid in aqueous solution with double quantity of alkali and subsequent neutralization leads to corresponding carboxylic acid obtaining. It was confirmed that the greatest outputs of salts as the reaction products were observed when using water as the solvent with the subsequent replacement of acetone. the optimum conditions of obtaining salts of 5-(2-bromophenyl)-4-amino-4H-1,2,4-triazole-3-ylthio)acetic acid with inorganic and organic bases were determined.